(untitled) - Jacobs, Carlynn Melissa

Evaluation of foliar fungicides for the control of mycotoxigenic fungi associated with Fusarium head blight of wheat in South Africa (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.